Ultra-central lung tumors: safety and efficacy of protracted stereotactic body radiotherapy. (3rd August 2021) - Lodeweges, Joyce E.; van Rossum, Peter S. N.; Bartels, Marcia M. T. J; van Lindert, Anne S. R.; Pomp, Jacqueline; Peters, Max; Verhoeff, Joost J. C.
Abstract: Background: For patients with early stage or medically inoperable lung cancer, stereotactic body radiotherapy (SBRT) is a general accepted and effective treatment option. The role of SBRT in ultra-central tumors remains controversial. The aim of this single-center retrospective analysis was to evaluate the safety and efficacy of protracted SBRT with 60 Gy in 12 fractions (with a biological effective dose (BED10 ) of 90–150 Gy) for patients with ultra-central lung tumors. Materials and methods: Patients with ultra-central lung tumors treated in our institution with 60 Gy in 12 fractions from January 2012 until April 2020 were included. Ultra-central tumors were defined as planning target volume (PTV) abutting or overlapping the main bronchi and/or trachea and/or esophagus. Data regarding patient-, tumor-, and treatment-related characteristics were evaluated. Results: A total of 72 patients met the criteria for ultra-central tumor location. The PTV abutted the main bronchus, trachea or esophagus in 79%, 22% and 28% of cases, respectively. At a median follow-up of 19 months, 1- and 2-year local control rates were 98% and 85%, respectively. Overall survival rates at 1 and 2 years were 77% and 52%, respectively. Grade 3 or higher toxicity was observed in 21%, of which 10 patients (14% of total) died of bronchopulmonary hemorrhage. A significant difference between patients with or without grade ≥3 toxicity was found for the mean dose ( D mean ) to the main bronchus ( p = 0.003), where a D mean BED3 of ≥91 Gy increased the risk of grade ≥3 toxicity significantly. Discussion: A protracted SBRT regimen of 60 Gy in 12 fractions for ultra-central lung tumors leads to high local control rates with toxicity rates similar to previous series, but with substantial risk of fatal bronchopulmonary hemorrhage. Therefore, possible risk factors of bronchopulmonary hemorrhage such as dose to the main bronchus should be taken into account.